Reversal of sensory deficit through sacral neuromodulation in an animal model of fecal incontinence. Issue 5 (28th January 2016) - Evers, J.; Devane, L.; Carrington, E. V.; Scott, S. M.; Knowles, C. H.; O'Connell, P. R.; Jones, J. F. X.
Abstract: Background: Sacral neuromodulation (SNM) is a treatment option for intractable fecal incontinence. The mechanism of action is unclear, however, increasing evidence for afferent somatosensory effects exists. This study's aim was to elucidate effects of acute SNM on the cerebral cortex in a rodent model of pudendal nerve injury. Methods: The effects of 14 Hz and 2 Hz SNM on sensory cortical activation were studied. In 32 anesthetized rats, anal canal evoked potentials (EPs) were recorded over the primary somatosensory cortex. Pudendal nerve injury was produced by 1‐hour inflation of two intra‐pelvic balloons. Four groups were studied: balloon injury, balloon injury plus either 14 Hz or 2 Hz SNM, sham operation. Immunohistochemistry for the neural plasticity marker polysialylated neural cell adhesion molecule (PSA‐NCAM) positive cells (numerical density and location) in the somatosensory cortex was performed. Key Results: Anal EP amplitudes diminished during balloon inflation; 14 Hz SNM restored diminished anal EPs to initial levels and 2 Hz SNM to above initial levels. Evoked potential latencies were prolonged during balloon inflation. The numerical density of PSA‐NCAM positive cells increased in the SNM groups, but not in sham or balloon injury without SNM. Stimulated cortices showed clusters of PSA‐NCAM positive cells in layers II, IV, and V. Post SNM changes were similar in both SNM groups. Conclusions & Inferences: Sacral neuromodulation augments anal representation in the sensory cortex and restores afferent pathways following injury. PSA‐NCAM positive cell density is increased in stimulated cortices and positive cells are clustered in layers II, IV, and V. Abstract : The study presented investigated the effect of sacral neuromodulation on anal canal somatosensory evoked potentials in a rodent model of fecal incontinence. Sacral neuromodulation restored anal evoked potentials diminished by pudendal nerve injury and stimulation at 2 Hz (optimum in healthy rats) was more effective than 14 Hz (therapeutic frequency). Sacral neruromodulation also increase expression of PSA‐NCAM, a marker for synaptic plasticity, in the somatosensory cortex.